Проекты урегулирования и основные политические решения крымскотатарской проблемы в 1970-80 гг. - Бекирова, Г.Т. (Культура народов Причерноморья, 2013)
В статье рассматриваются проекты советских партийно-советских органов по
политическому решению крымскотатарской проблемы, которые были направлены на удержание его в
местах спецпоселений и недопущению возвращения на историческую родину. Анализируется роль
национального движения крымских татар, содержание законодательных актов, которые издавались
под различными грифами секретности и носили явный дискриминационный характер. У статті розглядаються проекти радянських партійно-радянських органів з політичного
рішення кримськотатарської проблеми, які були направлені на утримання кримськотатарського народу
у місцях спецпоселеннь й не допущення до повернення на історичну батьківщину. Аналізується роль
національного руху кримських татар, змісту законодавчих актів, які видавались під різними грифами
секретності та носили явний дискримінаційний характер. The article deals with the projects of the Soviet party and government bodies on the political solution
to the Crimean Tatar problem, that were designed to hold the people in the places of special settlements and to
deter them from returning to their historical homeland. The role of the national movement of the Crimean
Tatars, the content of legislative acts, which were published under different security classifications and were
clearly discriminatory are analyzed. Forms of address of the Party-soviet bodies of the Ukrainian SSR to the
USSR central authorities to establish a legislative framework aimed at limiting and a complete ban on the return
of the Crimean Tatars to the Crimea. The actions of similar authorities of the Uzbek SSR, where the majority of
the deported Crimean Tatars lived, on the "rooting", practical measures aimed at weakening and discrediting
the national movement of the Crimean Tatars. In particular, the activities on organized resettlement of certain
Crimean Tatar families, only the representatives of the working professions, to the steppe areas of the Crimean
region in order to create the illusion of their national problem being solved at the state level. The author
considers and analyzes the content of legal and regulatory acts of central and republican (the Ukrainian SSR
and the Uzbek SSR) government authorities, declassified in the early 90s of the last century, the time and the
conditions in which they were created. The author draws a direct correlation between their appearance and the
activation of the national movement for the return to the historic homeland and restoration of the full range of
rights of the Crimean Tatar people, the strengthening of repressive measures against those who returned to the
Crimea independently